2016
DOI: 10.1093/gbe/evw016
|View full text |Cite
|
Sign up to set email alerts
|

Horizontal Gene Acquisitions, Mobile Element Proliferation, and Genome Decay in the Host-Restricted Plant PathogenErwinia Tracheiphila

Abstract: Modern industrial agriculture depends on high-density cultivation of genetically similar crop plants, creating favorable conditions for the emergence of novel pathogens with increased fitness in managed compared with ecologically intact settings. Here, we present the genome sequence of six strains of the cucurbit bacterial wilt pathogen Erwinia tracheiphila (Enterobacteriaceae) isolated from infected squash plants in New York, Pennsylvania, Kentucky, and Michigan. These genomes exhibit a high proportion of rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
67
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
2

Relationship

3
6

Authors

Journals

citations
Cited by 46 publications
(71 citation statements)
references
References 84 publications
3
67
0
1
Order By: Relevance
“…Numerous epidemiological studies of human pathogens have demonstrated environmental or zoonotic origins, but there are fewer studies of bacterial plant pathogens (Almeida and Nunney 2015;Andam et al 2016;Cauchemez et al 2016;Clarke et al 2015;Mather et al 2013;McCann et al 2013;Monteil et al 2016;Quibod et al 2016;Schwartz et al 2015;Shapiro et al 2016;Stukenbrock and Bataillon 2012;Vinatzer et al 2014;Wagner et al 2014;Arango Isaza et al 2016;Depotter et al 2017;Islam et al 2016;Menardo et al 2016). Where ecological and genetic factors restrict pathogens to a small number of plant hosts greater progress has been made, but for facultative pathogens such as P. syringae that colonize multiple hosts and are widely distributed among both plant and nonplant habitats, the environmental reservoirs of disease and factors affecting their evolutionary emergence are difficult to unravel (Singh et al 2011;Monteil et al 2016).…”
Section: Dynamic Genome Evolution Of Psa-3mentioning
confidence: 99%
“…Numerous epidemiological studies of human pathogens have demonstrated environmental or zoonotic origins, but there are fewer studies of bacterial plant pathogens (Almeida and Nunney 2015;Andam et al 2016;Cauchemez et al 2016;Clarke et al 2015;Mather et al 2013;McCann et al 2013;Monteil et al 2016;Quibod et al 2016;Schwartz et al 2015;Shapiro et al 2016;Stukenbrock and Bataillon 2012;Vinatzer et al 2014;Wagner et al 2014;Arango Isaza et al 2016;Depotter et al 2017;Islam et al 2016;Menardo et al 2016). Where ecological and genetic factors restrict pathogens to a small number of plant hosts greater progress has been made, but for facultative pathogens such as P. syringae that colonize multiple hosts and are widely distributed among both plant and nonplant habitats, the environmental reservoirs of disease and factors affecting their evolutionary emergence are difficult to unravel (Singh et al 2011;Monteil et al 2016).…”
Section: Dynamic Genome Evolution Of Psa-3mentioning
confidence: 99%
“…In all enterobacteria, expansin genes are unfused to carbohydrate active domains. However, the plant pathogens Erwinia tracheiphila (80, 100) and Pantoea stewartii have a canonical expansin gene directly adjacent to – but in a separate open reading frame (ORF) – from a GH5 endoglucanase gene. This expansin-GH5 domain arrangement in E. tracheiphila and P. stewartii is in opposite positional order to the 15 Xanthomonadaceae with a GH5-expansin fusion construct, suggesting that in either E. tracheiphila or P. stewartii this gene architecture arose de novo and was not acquired horizontally from a Xanthomonadaceae donor.…”
Section: Resultsmentioning
confidence: 99%
“…In the temperate Eastern United States, Acalymma vittatum can transmit the virulent bacterial pathogen, Erwinia tracheiphila . This pathogen does not occur anywhere else in the world outside of this limited geographic area, and inferences from E. tracheiphila genomics studies suggest it was human-mediated changes to cucurbit agro-ecosystems that recently drove its emergence in this region (Shapiro et al 2015, Shapiro et al 2016, Andrade-Domínguez et al 2018, Shapiro et al 2018a, Shapiro et al 2018b).…”
Section: Methodsmentioning
confidence: 95%
“…In temperate Eastern North America, both E. pruinosa and A. vittatum exclusively rely on domesticated plants grown in human managed agro-ecosystems as a food resource. Temperate Eastern North America is also the only region worldwide where A. vittatum transmits Erwinia tracheiphila Smith (Enterobacteriaceae), the causal agent of bacterial wilt of cucurbits, which causes millions of dollars annually in direct yield losses and indirect preventative measures (Shapiro et al 2014, Shapiro et al 2016, Shapiro et al 2018b). E. tracheiphila can persistently colonize the digestive tract of beetle vectors after beetles feed on the foliage of wilting, symptomatic plants (Rand and Enlows 1916, Rand and Cash 1920, Rand and Enlows 1920, Smith 1920, Shapiro et al 2012, Shapiro et al 2014).…”
Section: Introductionmentioning
confidence: 99%